Preterm birth and the risk of multimorbidity in adolescence: a multiregister-based cohort study - Heikkilä Katriina; Metsälä Johanna; Pulakka Anna; Nilsen Sara Marie; Kivimäki Mika; Risnes Kari; Kajantie Eero (Elsevier, 2025)
Background
Multimorbidity affects people of all ages, but the risk factors of multimorbidity in adolescence are unclear. The aim of this study was to examine preterm birth (<37 weeks) as a shared risk factor for multiple health outcomes and the role of gestational age (degree of prematurity) in the development of increasingly complex multimorbidity (two, three, or four health outcomes) in adolescence (age 10–18 years).
Methods
We used population-wide data from Finland (1 187 610 adolescents born 1987–2006) and Norway (555 431 adolescents born 1998–2007). Gestational age at birth was ascertained from medical birth registers and categorised as 23–27 weeks (extremely preterm), 28–31 weeks (very preterm), 32–33 weeks (moderately preterm), 34–36 weeks (late preterm), 37–38 weeks (early term), 39–41 weeks (term, reference category) and 42–44 weeks (post-term). Children who died or emigrated before their 10th birthday, and those with missing or implausible data on gestational age, birthweight, or covariates, were excluded. Health outcomes at age 10–18 years were ascertained from specialised health care and mortality registers. We calculated hazard ratios (HRs) and population attributable fractions (PAFs) with 95% CIs for multiple health outcomes during adolescence.
Findings
Individuals were followed up from age 10 to 18 years (mean follow-up: 6 years, SD: 3 years). Preterm birth was associated with increased risks of 20 hospital-treated malignant, cardiovascular, endocrinological, neuropsychiatric, respiratory, genitourinary, and congenital health outcomes, after correcting for multiple testing and ignoring small effects (HR <1·2). Confounder-adjusted HRs comparing preterm with term-born adolescents were 2·29 (95% CI 2·19–2·39) for two health outcomes (PAF 9·0%; 8·3–9·6), and 4·22 (3·66–4·87) for four health outcomes (PAF 22·7%; 19·4–25·8) in the Finnish data. Results in the Norwegian data showed a similar pattern. We observed a consistent dose–response relationship between an earlier gestational age and elevated risks of increasingly complex multimorbidity in both datasets.
Interpretation
Preterm birth is associated with increased risks of diverse multimorbidity patterns at age 10–18 years. Adolescents with a preterm-born background could benefit from diagnostic vigilance directed at multimorbidity and a multidisciplinary approach to health care.
Funding
European Union Horizon 2020, Academy of Finland, Foundation for Pediatric Research, Sigrid Jusélius Foundation, Signe and Ane Gyllenberg Foundation.